SIGNS OF CHANGES IN THE PEDAGOGICAL PRACTICE OF PHYSICAL EDUCATION TEACHERS: ANALYSIS OF STUDIES PUBLISHED IN PROCEEDINGS OF NATIONAL SCIENTIFIC EVENTS - Maldonado, Daniel Teixeira (2018)
The objective of this study was to understand the signs of changes in the pedagogical practices of Physical Education teachers, according to the research and educational experiences published in the proceedings of the main events in that area, carried out in Brazilian territory. A documentary research was carried out in 28 editions of six scientific events of Physical Education in the school, counting 2168 interpreted abstracts. We identify that many professors and researchers present and publish innovative educational experiences in the classroom, mainly in what concerns the diversification of the corporal practices developed. These educational projects happened, for the most part, in the public schools, in the Fundamental Education and were published in the last decade. We conclude that a new didactic-pedagogical tradition begins to emerge in the Physical Education classes in the daily school life.